ANALISIS PROSES MUAT KENDARAAN UNTUK MENCEGAH KETERLAMBATAN PEMUATAN DI KM. DHARMA RUCITRA VIII - Muhammad Abdul Chadir; Rizal Rochmansyah; Achmad Ali Mashartanto; Yusuf Pria Utama (STKIP Subang, 2026)
Vehicle loading and unloading operations are critical activities that directly affect ship departure schedules. This study aims to analyze the factors causing delays in vehicle loading operations and the mitigation efforts implemented on KM Dharma Rucitra VIII. The research employs a qualitative descriptive method, with data collected through field observations, interviews, documentation studies, and fishbone diagram analysis. The results indicate that vehicle loading delays are influenced by four main factors. The material factor is related to the presence of Over Dimension Over Load vehicles. The method factor arises from the absence of standardized procedures for checking vehicle dimensions and load limits. The environment factor includes tidal conditions and sea waves that affect ship stability during loading operations. The machine factor is associated with rampdoor loads exceeding the Safe Working Load of 45 tons. These factors are interrelated and disrupt the continuity of the vehicle loading process. Based on the fishbone analysis, several mitigation efforts are proposed, including monitoring weather forecasts and tidal conditions through the Maritime Meteorological Station, utilizing Indonesian tidal reference data, arranging vehicle loading based on priority, restricting over dimension over load vehicles, and implementing standardized checks of vehicle dimensions and loads prior to loading. The application of these measures is expected to improve safety, orderliness, and efficiency in vehicle loading operations, thereby minimizing delays in ship departures.